Antibiotic resistance in freshwater cyanobacteria and associated bacteria - Dias, Elsa (2014)
Objectives: Cyanobacteria are ubiquitous prokaryotes in aquatic ecosystems and although they can be exposed to antibiotics, their role on water resistome was never investigated. Thus, this work aimed to evaluate the antibiotic susceptibility patterns and resistance mechanisms of cyanobacteria and co-occurring bacteria in order to assess their contribution to the global pool of resistance determinants in freshwater. Methods: We investigated 4 cyanobacterial genera (Microcystis, Aphanizomenon, Anabaena and Planktothrix), previously isolated from freshwater reservoirs, and several bacteria isolated from those cyanobacterial cultures. Antibiotic susceptibility of cyanobacteria was evaluated by microdilution method, under specific culturing conditions, against beta-lactams, aminoglycosides, quinolones, sulfonamides and tetracyclines. Minimum inhibitory concentrations (MIC) were determined according to cyanobacterial cell dentisty (DO, 450nm) and microscopic examination of cultures integrity. Bacteria were identified by 16S sequencing and their susceptibility patterns were determined by disk diffusion, according to SFM 2012 non-specific breakpoints, against the same antibiotics. All strains were subjected to the search of class 1, 2 and 3 integrons and antibiotic resistance genes according to the phenotype. Results: Overall, we observed a great diversity of susceptibility to the tested antibiotics, among the distinct strains. Microcystis showed the lowest susceptibility regarding beta-lactams. Conversely, Microcystis was more susceptible to quinolones, while Planktothrix showed higher MIC values. Bacteria from cyanobacterial cultures were identified as Hydrogenophaga atypica, Limnobacter thioxidans, Rhizobium radiobacter, Sphingobium sp. and Brevundimonas lenta. Even though no known antibiotic resistance genes were yet identified, bacteria from different species and showing distinct phenotypes exhibited class 1 and 2 integrons. L. thioxidans, for example, revealed to be resistant to aminoglycosides and harbored a class 2 integron. Conclusions: Although no known antibiotic resistance genes were found in cyanobacteria and co-occurring bacteria, the presence of integrons and the susceptibility to antibiotics, suggest that they may play a role on freshwater resistome and eventually contribute to the dissemination of antibiotic resistance. These results may also be helpful to define guidelines and breakpoints to access cyanobacteria antibiotic susceptibility.